The effect of satisfying basic psychological needs of workers in public organizations on job attitudes and turnover intention: Focused on generation gap - Kim, 가람; Jang, 상원; Park, 지훈; Choi, 은수 (Korean Journal of Industrial and Organizational Psychology, 2023)
Recently, the high turnover rate of MZ generation public employees has emerged as a serious problem for public organizations in Korea, and it is necessary to explore the underlying reasons. This study aimed to explain job satisfaction, organizational commitment, and turnover intention of public organizational workers in the perspective of basic psychological needs satisfaction in the workplace by generation. In other words, this study examined whether the basic psychological needs satisfaction by generation affects job satisfaction and organizational commitment, and further predicts turnover intention. A survey was conducted on 205 public organizational workers. Findings demonstrated that the interaction effect of the generation was significant in the relationship between basic psychological need satisfaction and work attitudes. Specifically, among workers in public institutions, in the older generation, the satisfaction of autonomy and relatedness in the workplace increased job satisfaction and organizational commitment, and finally lowered turnover intention. On the other hand, in the MZ generation, the satisfaction of competence increased both job satisfaction and organizational commitment, and the satisfaction of relatedness increased organizational commitment, thus finally lowered turnover intention. This study discusses the theoretical implications of the generation gap in the influence of basic psychological needs, as well as the practical implication to suggest an insight for an intervention program to prevent the turnover of workers in public organizations.